Two novel isoflavone derivatives from Ficus esquiroliana Levl. and their cytotoxic effects on cancer cells. (December 2022) - Dai, De-Cai; Xu, Xue-Feng; Yan, Hao; Zhang, Yu
Abstract: Two novel isoflavone derivatives ficusavone A and B (1 and 2 ) together with two known biogenetically related isoflavone derivatives (3 and 4 ) were isolated from the stems of Ficus esquiroliana Levl. The structures of these compounds were elucidated using comprehensive spectroscopic methods. Compounds 1 and 2 represent the rare example of an isoflavone derivative of oxidative cracking of isopentene from natural products. The inhibitory activities of all compounds against HeLa, MCF-7 and A549 cells were evaluated. Compound 1 showed the cytotoxicity against the MCF-2 (IC50 = 12.3 μ M) and A549 (IC50 = 17.8 μ M) cell lines. The other compounds showed modest activities or were inactive. Graphical Abstract: ga1 Highlights: A phytochemical study of Ficus esquiroliana EtOH extract was carried out. Two novel isoflavone derivatives ficusavone A and B were isolated and characterized. Compound 1 showed the cytotoxicity against the MCF-2 (IC50 = 12.3 μ M) and A549 (IC50 = 17.8 μ M) cell lines.